(untitled) (IF-Sophia: revista eletrônica de investigações Filosófica, Científica e Tecnológica, 2018)
This article aims to question the traditional way of teaching the origin of Philosophy and the passage from myth to reason that are usually presented in Philosophy courses in High School, indicating the educational damages that such an approach causes in students, as to learning and development of philosophical skills. As much as, to point out the training difficulties that most Philosophy teachers graduates in the field have, due to insufficient training in Ancient Philosophy and even more, teachers from other areas who teach Philosophy. This entails irreparable damage to students in the learning of Philosophy and its citizen experience. In order to do so, the unacceptable and common understanding of myth, usually taught in Colleges and sometimes even in some institutions of Higher Education, will be emphasized. Finally, the relation between myth and reason in pre-Socratic philosophy will be indicated here, seeking to collaborate in the formation of colleagues in the philosophical magisterium and perhaps to modify the general understanding of the myth-reason problem.